[OA219] Eye lens dose monitoring in interventional radiology. (August 2018) - Scalchi, Paolo; Magagna, Jessica; Montenegro, Giuseppe Mansi; Beghetto, Mario; Boi, Luca; Dall'Acqua, Jacopo; Francescon, Paolo; Savastano, Sergio
Abstract : Purpose: The new limit established for the eye lens has increased the interest for lens dose monitoring. This work aims to: Estimate the lens doses for the staff of the Interventional Radiology department at Vicenza Hospital; Establish relationships between the eye lens dose and the dose measured with personal dosimeters; Verify the feasibility of using commercial Hp (3) dosimeters; Investigate a possible relationships between the lens dose and the air Kerma–Area product (KAP). Methods: Measurements have been carried out both in vivo (4 radiologists and 5 nurses) during 87 different abdominal procedures performed with a Multistar (Siemens, Germany), and in anthropomorphic-phantom using a single 180° projection at 59 kV and 125 kV. The evaluations included: Hp (10) and Hp (0.07) measurements performed at the chest level over the apron (Hp, chest ); Hp (0.07) measurements performed on the external and inferior sides of the left eye using Hp (0.07) detectors specifically modified for this purpose (Hp, eye ); Hp (3) performed with dedicated dosimeters positioned over the left arm of the protective glasses (Hp, glasses ). Additional Hp (0.07) measurement were performed directly at the phantom eye lens level (Hp, lens ). Transmission factors of the lead glasses were also estimated. Results: The main results are: Hp, eye /Hp, chest : 0.6 ± 0.6 ( in vivo ); 0.4 ± 0.2 (in phantom) Hp, eye /Hp, glasses : 1.1 ± 1.2 ( in vivo ); 0.5 ± 0.5 (in phantom) Hp, chest /KAP: 2.5 ± 3.6 μSv Gy −1  cm −2 ( in vivo ); 5.8 ± 2.0 μSv Gy −1  cm −2 (in phantom) In vivo and phantom results are consistent within the large uncertainties due to low dose levels and irradiations variability. Therefore phantom measurements allowed estimating Hp, lens /Hp, eye in 0.20 when glasses are used. Using this factor, the projected annual eye lens dose, considering the workload, resulted 4 mSv for the personnel using lead glasses and 15 mSv for the others. The ratio between eye lens dose with and without glasses is higher than expected based on transmission factors. Conclusions: According to our results, traditional monitoring methods with proper corrections could be used to estimate lens dose in place of expensive Hp (3) dosimeters. Missing glasses-skin contact could explain eye doses higher than expected.